(Un)stable relations : horses, humans and social agency - Birke, Lynda; Thompson, Kirrilly (London : Routledge, 2018)
"This original and insightful book explores how horses can be considered as social actors within shared interspecies networks. It examines what we know about how horses understand us and how we perceive them, as well as the implications of actively recognising other animals as actors within shared social lives. This book explores how interspecies relationships work, using a variety of examples to demonstrate how horses and people build social lives. Considering horses as social actors presents new possibilities for improving the quality of animal lives, the human condition and human-horse relations."--Provided by publisher.
chapter Introduction -- part Part I Theorising horses -- chapter 1 Equine co-travellers -- chapter 2 Animals as social actors -- part Part II Thinking horses -- chapter 3 Natural horses -- chapter 4 Symbolic horses -- chapter 5 Equestrian cultures -- part Part III Meeting horses -- chapter 6 Choreographies -- chapter 7 Moving with motive -- part Part IV Engaging horses -- chapter 8 Agency matters -- chapter 9 (Un)stable relations.
Keywords: Human-animal relationships; Horses -- Social aspects; Horses -- Psychological aspects